Routine (an)isotropic crystallite size analysis in the double-Voigt approximation done right? - Ectors, Dominique; Götz-Neunhoeffer, Friedlinde; Neubauer, Jürgen (Powder Diffraction, 2017)
In this study, the application of (an)isotropic size determination using a recently proposed model for the double-Voigt approach is demonstrated and validated against line profile simulations using the Whole Powder Pattern Modelling approach. The fitting of simulated line profiles demonstrates that the attained crystallite sizes and morphologies are in very reasonable agreement with the simulated values and thus demonstrate that even in routine application scenarios credible size and morphology information can be obtained using the double-Voigt approximation. The aim of this contribution is to provide a comprehensive introduction to the problem, address the practical application of the developed model, and discuss the accuracy of the double-Voigt approach and derived size parameters. Mathematical formulations for the visualization of modeled morphologies, supporting the application of the recently developed macros, are additionally provide
Keywords: anisotropic crystallite size; double-Voigt; Rietveld; size–strain; TOPAS